GRB 190530A: From Precursor, Prompt Emission to Afterglow all Originated from Synchrotron Radiation. (1st June 2022) - Liu, Hui-Ya; Wang, Xiang-Gao; Xin, Li-Ping; Zhou, Zi-Min; Chen, Liang-Jun; Li, Bing; Yang, Yuan-Gui; Luo, Qi; Li, Cheng-Kui; Xiong, Shao-Lin; Wang, Ling-Jun; Han, Xu-Hui; et al.
Abstract: GRB 190 530A was jointly observed by the High Energy X-ray Telescope of the Hard X-ray Modulation Telescope (Insight-HXMT/HE) and the Ground-Based Wide-Angle Camera network (GWAC-N) with the extremely large field of view. After triggered by Insight-HXMT/HE and Fermi/GBM, we observed the optical emission of GRB 190 530A, using the 30 cm telescope of GWAC (GWAC-F30) to search and locate its position. Subsequent observation of the late afterglow of GRB 190 530A was made with the 2.16 m telescope at Xinglong Observatory. In this paper, we make a detailed exploration of the origin of GRB 190 530A. In the prompt emission, a "double-tracking" pattern is presented both for the low-energy spectral index α and the peak energy E p in the Band function with Insight-HXMT/HE and Fermi/GBM data; the results of GRB 190 530A are consistent with the Amati and Yonetoku correlations; the spectral lag ( τ ) versus energy ( E ) can be estimated with τ = − 3.0 ± 0.06 + ( 0.17 ± 0.03 ) log E . The synchrotron radiation can account for the origin of GRB 190 530A prompt emission behaviors. The α and E p of the precursor are essentially the same as that of the main prompt emission, implying that they have the same origin. For the afterglow, it can be described with the external forward shock model in ISM circumburst medium. In summary, from precursor, prompt emission to afterglow of GRB 190 530A all originated from synchrotron radiation.